The duration of family-related employment interruptions - the~role~of occupational characteristics - Ann-Christin Bächmann; Dörthe Gatermann (Journal for Labour Market Research, 2017)
After childbirth, women often interrupt their careers. These interruptions are associated with negative consequences for later employment, which are greatly influenced by the duration of the interruption. We analyse the influence of occupational characteristics on this duration, as occupations are crucially important for career trajectories in Germany. Specifically focusing on occupational sex segregation, the occupational wage level and the share of part-time workers in occupations, we test two competing hypotheses: on the one hand, lower wages in female-dominated occupations should lead to longer employment interruptions due to lower opportunity costs. On the other hand, a higher ratio of part-time workers should lead to shorter interruptions due to better reconciliation between family and work. In addition, we analyse whether the proportion of women in a given occupation influences the duration of employment interruptions. We test these hypotheses using data from the National Educational Panel Study (starting cohort 6), combined with occupational information from the Sample of Integrated Labour Market Biographies and the German Microcensus. We focus on family-related employment interruptions after the birth of the first child between 1992 and 2010. The results of our discrete event history models indicate that higher wages lead to shorter breaks, while the part-time rate and the proportion of women in an occupation have no significant effects. – – Nach der Geburt eines Kindes unterbrechen viele Frauen ihre Erwerbstätigkeit. Diese familienbedingten Erwerbspausen führen zu Karrierenachteilen, deren Ausmaß entscheidend von der Dauer der Unterbrechung abhängt. Aufgrund der nachhaltigen Bedeutung des Berufs für den gesamten Erwerbsverlauf in Deutschland untersuchen wir, inwieweit berufliche Merkmale diese Dauer beeinflussen. Dabei konzentrieren wir uns auf den Effekt beruflicher Geschlechtersegregation und die damit einhergehenden Berufsmerkmale Lohnniveau und Teilzeitquote und testen gegenläufige Hypothesen: Einerseits sollte das geringere Lohnniveau in frauendominierten Berufen durch niedrigere Opportunitätskosten zu längeren Erwerbsunterbrechungen führen. Andererseits sollten sich hohe Teilzeitquoten in frauendominierten Berufen aufgrund der besseren Vereinbarkeitsmöglichkeiten verkürzend auf Erwerbsunterbrechungen auswirken. Zudem wird untersucht, ob der Frauenanteil selbst darüber hinaus einen eigenständigen Effekt auf die Unterbrechungsdauer aufweist. Wir testen diese Hypothesen anhand von Daten des Nationalen Bildungspanels (Startkohorte 6), die um berufliche Merkmale beruhend auf der Stichprobe der Integrierten Arbeitsmarktbiographien und des Mikrozensus erweitert werden. Wir betrachten dazu Erwerbsunterbrechungen nach der Geburt des ersten Kindes in den Jahren 1992 bis 2010. Anhand von diskreten Ereignisdatenmodellen zeigt sich, dass ein hohes berufliches Lohnniveau die Rückkehr von Müttern auf den Arbeitsmarkt beschleunigt, während der Teilzeitanteil und der Frauenanteil selbst keinen signifikanten Einfluss aufweisen.
Keywords: J13; J16; J24; 330; Female employment; Family related employment interruptions; Occupational sex segregation; Event history analysis; West Germany